Extreme Runoff of Chemical Species of Nitrogen and Phosphorus Threatens a Florida Barrier Island Lagoon - Trefry, John H.; Fox, Austin L. (Frontiers in Marine Science, 2021)
Extreme runoff of stormwater to poorly flushed barrier island lagoons often adds excess nitrogen (N) and phosphorus (P) that can promote subsequent, sometimes intense, harmful algal blooms (HABs). Successful management of such estuaries requires special appreciation of when and how to control concentrations and fluxes of chemical species of N and P during high flow. Toward that end, monthly surveys and episodic rain-event sampling were carried out from December 2015 to March 2018 for two contrasting tributaries of the Indian River Lagoon (IRL), a barrier island lagoon in Florida. One tributary, South Prong Saint Sebastian River, flows through predominantly agricultural, forested and open land, whereas the second tributary, Crane Creek, traverses mainly residential-commercial land. Concentrations of some N and P species in these tributaries increased with increased flow and could be described with statistically significant equations for concentration versus flow rate, thereby supporting flow-rate-dependent flux determinations. Drainage basin yields (fluxes per square km) varied with land cover/use. Calculated annual yields of dissolved organic N (DON) and dissolved inorganic P (DIP) averaged ∼70% greater for South Prong Saint Sebastian River from high flow through thicker, more organic- and P-rich soils. In contrast, yields of nitrate + nitrite were 100% higher for Crane Creek from widespread application of N-fertilizer to thin layers of turfgrass overlying sand, plus runoff of N-rich reclaimed water. Two major weather events highlighted our study and foreshadow impacts from climate change. Seven months of drought from November 2016 to May 2017 were followed in September-October 2017 by excess rain, runoff and flooding from Hurricane Irma. Consequently, >50% of freshwater fluxes and ∼60% of N and P fluxes from South Prong Saint Sebastian River, Crane Creek and other IRL tributaries occurred during 2 months in 2017. Lagoon-wide inputs provided enough bioavailable N and P to help support a nanoeukaryotic bloom for >5 months, with chlorophyll a values >50 μg L–1. The bloom was co-dominated by the brown tide alga, Aureoumbra lagunensis, and an unidentified nanoeukaryotic green alga. Decreased salinity, low concentrations of dissolved inorganic N and P, and decreasing dissolved organic P (DOP), combined with biological factors, diminished the IRL bloom by mid-2018.